The Effect of Responsiveness and Perceived Service Quality on Customer Satisfaction in MSMEs Batik in Semarang City - Nafisah, Fina Raudlotun; Yunaidi, Eri; Wahyudi, Sugeng (LifeSciFi, 2024)
This study aims to analyze the relationship between responsiveness and perceived service quality in relation to customer satisfaction within Micro, Small, and Medium Enterprises (MSMEs) Batik. Responsiveness is defined as the ability of MSMEs to respond quickly and accurately to customer needs and complaints, while perceived service quality refers to how customers perceive the quality of service they receive. A quantitative method was used in this research, with data collected through questionnaires distributed to 200 customers from various MSME sectors batik. The regression analysis results indicate that responsiveness has a positive and significant effect on perceived service quality. In other words, the more responsive MSMEs are in addressing customer needs, the higher the customer perception of the service quality. This improved perception of service quality directly contributes to higher customer satisfaction. These findings emphasize the importance of speed and accuracy in delivering services to enhance customers' positive experiences. Furthermore, the study highlights the importance of improving responsiveness and perceived service quality as key strategies for strengthening customer satisfaction and loyalty in MSMEs. Enhancing both aspects will help MSMEs compete more effectively in a competitive market. Therefore, MSME managers should focus on optimizing responsiveness and perceived service quality to maintain business sustainability and competitiveness.